Questions of beauty of the nature in the scientific and philosophical heritage of V. I. Vernadsky - Karako, Petr S. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article deals with the process of the formation of the aesthetic relation to the nature of V. I. Vernadsky. It is noted the role and place of literature and music in the scientific and philosophical comprehension of the nature. Particular attention is paid to the analysis of his contribution to the identification of equilibrium and harmonious relationship between the structural components of the biosphere, their symmetry as the foundation of its beauty. It emphasizes the importance of taking into account the aesthetic aspect of the biosphere in the analysis of its current state, and the transition into the noosphere. Attention is drawn to the fact that the implementation of the aesthetic ideas of the Russian scientist and thinker in the modern scientific knowledge leads to the formation of a new scientific discipline – environmental aesthetics.